2012
DOI: 10.1002/alr.21083
|View full text |Cite
|
Sign up to set email alerts
|

The presentation and clinical significance of sinonasal respiratory epithelial adenomatoid hamartoma (REAH)

Abstract: Isolated REAH, which may mimic a neoplasm, appears to be a different clinical entity than the more common form encountered in association with nasal polyps and inflammation. Further investigation into the etiology and clinical significance is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 14 publications
3
68
0
2
Order By: Relevance
“…6 A range of 61% to 73% of REAH is found in conjunction with an inflammatory process, especially NP. [1][2][3] REAH can also be presented in two forms: isolated lesion (less frequent) or in association with another inflammatory process. 1,2,13 In the latter form, a significant association was found between REAH-OC and the following: 1) asthma, 2) a long history of NP, and 3) previous surgery for NP.…”
Section: Introductionmentioning
confidence: 99%
“…6 A range of 61% to 73% of REAH is found in conjunction with an inflammatory process, especially NP. [1][2][3] REAH can also be presented in two forms: isolated lesion (less frequent) or in association with another inflammatory process. 1,2,13 In the latter form, a significant association was found between REAH-OC and the following: 1) asthma, 2) a long history of NP, and 3) previous surgery for NP.…”
Section: Introductionmentioning
confidence: 99%
“…We now know that REAH is not as uncommon as originally thought and is often present with other infl ammatory processes (3). In a case series, 73% of 45 patients with REAH had an additional associated pathological process, most commonly nasal polyposis (NP) (9). Recent studies have shown that REAH was found in 35% to 47% of patients with NP who were treated surgically (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, the origin of REAHs in the olfactory cleft (REAH‐OC) was first reported . They are frequently observed inside the OC of patients with nasal polyposis, especially in those with previous sinus surgery …”
Section: Introductionmentioning
confidence: 99%
“…3 They are frequently observed inside the OC of patients with nasal polyposis, 2-5 especially in those with previous sinus surgery. 4,5 Histopathologically, REAHs can be confused with malignant tumours, especially in the case of small biopsies. 6…”
Section: Introductionmentioning
confidence: 99%